Prevalence of Acute Appendicitis Complications in Overweight and Obese Patients: A Cross-Sectional Case Series Study - Ahmed, Bawan Muhamad Jazaa; Ahmed, Hiwa Omer (Sulaimani Journal for Pure and Applied Sciences, 2022)
Background: Obesity is known to increase morbidity and mortality in the general population and therefore is perceived as a risk factor for adverse post-surgical results. Aims: To find the real impact of extra weight on the course of the early postoperative complications of open appendectomy. Methods: A prospective cross-sectional case series study was conducted on 93 patients from a total 100 patients labeled with an acute abdomen with signs and symptoms of acute appendicitis. Early postoperative complications are classified according to the Clavien-Dindo-Classification (CDC) system. Results: Seventy-one (76.34%) patients went through a smooth postoperative period without complications, of which the majority belong to group A with normal body weight (n=39, 54.9%). The most common early complications were superficial surgical site infection (n=14, 15.05), deep surgical site infection (n=6, 6.45%) equally in both groups A, and B that required hospital admission and antibiotic therapy and 2 male patients (2.15%) in the group A; average weight group developed deep surgical site infection both of their intraoperative findings were perforated appendicitis. Conclusions: There is a significant relationship between the duration of hospital stay and the patient's weight (P-value=0.00541). Albeit, the results showed that patients with excess weight need to stay longer in the hospital compared to average-weight patients.
Keywords: Appendicitis; early complications; excess weigh; hospitalizatio; prospective cross-sectional study